Model Pengelolaan Tanah Wakaf di Kota Semarang - Yasin Arief S.; Tali Tulab (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2018)
Waqf in Indonesia is one of the Islamic institutions related to the welfare of the ummah and has long been institutionalized. The problems arising from some of the wakaf practices in the community are not only about the implementation of wakaf, but also in the management of wakaf land in accordance with the principles of sharia. The implementation of wakaf in Semarang City is similar to the management in other areas. Wakaf trends in the community are still around mosques, schools and tombs as objects of waqf. The results of research indicate that the practice of waqf in KUA is still waqf about the land. data in the field indicates, that allotment of musholla as much as 49%. While the mosque as much as 27%. Schools and pesantren are 13% and 3%. Tombs of 3% and other social institutions as much as 5%. As for the condition of wakaf land, as many as 79% of existing wakaf land has been certified. Meanwhile, 21% is only limited to the deed of pledge of waqf.Keyword: Model, Management, Waqf, Semarang